Psychological characteristics of victim behavior of women in situations of domestic violence - Лефтеров, Василь Олександрович; Лефтеров, В. О.; Лефтеров, Василий Александрович; Lefterov, Vasyl O.; Вакуліч, Тетяна Михайлівна; Вакуліч, Т. М.; Вакулич, Татьяна Михайловна; Vakulich, Tetiana M. (Moscow State University of Psychology and Education, 2013)
The article deals with analysis of psychological factors and characteristics of victim behavior of women in situations of domestic violence. We considered prerequisites for the formation of victim behavior in women, motives and psychological implication of protective mechanisms of women in a dysfunctional family. It is noted that the victimized women are inclined to sacrifice their "I" in order to be accepted by family system and this characteristic belongs to the general features of victimization, which manifests itself in disadaptive behavior of subjects. We revealed and described the psychological characteristics of victim behavior of women in situations of domestic violence, including neuroticism, affective functions disorder, state of learned helplessness, cognitive disorders, deformed self-perception and low self-esteem, proneness to conflict and contradictions, post-traumatic stress disorder, boundary violations of “Ego”, traumatic childhood experiences and behaviors of parents.

Стаття присвячена теоретичному аналізу психологічних факторів та особливостей віктимної поведінки жінок у ситуаціях домашнього насильства. Розглянуто передумови формування віктимної поведінки жінок, мотиви та прояви захисних психологічних механізмів у жінок за умов дисфункціональної сім'ї. Відзначено, що віктимні жінки схильні жертвувати своїм «Я», щоб бути прийнятими сімейною системою, і ця характеристика належить до рис загальної віктимності, що виявляється у дезадаптативній поведінці суб'єкта. Виділено та охарактеризовано психологічні особливості віктимної поведінки жінок у ситуаціях домашнього насильства, серед яких невротизованість, розлади афективних функцій, стан навченої безпорадності, розлади когнітивних функцій, деформоване самосприйняття та занижена самооцінка, конфліктність та суперечливість, посттравматичний досвід дитинства та моделі поведінки батьків.

Статья посвящена теоретическому анализу психологических факторов и особенностей виктимного поведения женщин в ситуациях домашнего насилия. Рассмотрены предпосылки формирования виктимного поведения женщин, мотивы и проявления защитных психологических механизмов у женщин в условиях дисфункциональной семьи. Отмечено, что виктимные женщины склонны жертвовать своим «Я», чтобы быть принятыми семейной системой, и эта характеристика принадлежит к чертам общей виктимности, проявляющейся в дезадаптативном поведении субъекта. Выделены и охарактеризованы психологические особенности виктимного поведения женщин в ситуациях домашнего насилия, среди которых невротизированность, расстройства аффективных функций, состояние обученной беспомощности, расстройства когнитивных функций, деформированное самовосприятие и заниженная самооценка, конфликтность и противоречивость, посттравматическое стрессовое расстройство, нарушение границ «Эго», психотравмирующий опыт детства и модели поведения родителей.
Психологические особенности виктимного поведения женщин в ситуациях домашнего насилия
Lefterov V. A. Psychological characteristics of victim behavior of women in situations of domestic violence / V. A. Lefterov, T. M. Vakulich // Psychology and Law. - Vol. 3, №. 2. - Moscow State University of Psychology and Education, 2013. - 11 р.
Keywords: psychological characteristics; victim behavior; female victims; domestic violence; dysfunctional family; marital relationship; protective psychological mechanism; психологічні особливості; віктимна поведінка; жінки-жертви; домашнє насильство; дисфункціональна сім'я; подружні стосунки; захисний психологічний механізм; психологические особенности; виктимное поведение; женщины-жертвы; домашнее насилие; дисфункциональная семья; супружеские отношения; защитный психологический механизм; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology